2015
DOI: 10.1189/jlb.3a0415-155rr
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane inhibits multiple inflammasomes through an Nrf2-independent mechanism

Abstract: The inflammasomes are intracellular complexes that have an important role in cytosolic innate immune sensing and pathogen defense. Inflammasome sensors detect a diversity of intracellular microbial ligands and endogenous danger signals and activate caspase-1, thus initiating maturation and release of the proinflammatory cytokines interleukin-1β and interleukin-18. These events, although crucial to the innate immune response, have also been linked to the pathology of several inflammatory and autoimmune disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 80 publications
(123 reference statements)
9
101
0
1
Order By: Relevance
“…These findings are supported by other groups describing Nrf2 independent effects of SFN in e.g. in cycle arrest and apoptosis, and inhibition of angiogenesis, histone deacetylases and cytochrome P450 [31]. Recently Greaney et al ., 2015 focused studies on inflammasomes, as these have an important role in cytosolic innate immune sensing and pathogen response.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings are supported by other groups describing Nrf2 independent effects of SFN in e.g. in cycle arrest and apoptosis, and inhibition of angiogenesis, histone deacetylases and cytochrome P450 [31]. Recently Greaney et al ., 2015 focused studies on inflammasomes, as these have an important role in cytosolic innate immune sensing and pathogen response.…”
Section: Discussionsupporting
confidence: 74%
“…Recently Greaney et al ., 2015 focused studies on inflammasomes, as these have an important role in cytosolic innate immune sensing and pathogen response. They found that SFN-mediated inhibition of inflammasomes is also independent of Nrf2 [31]. Other evidence points to SFN reacting directly with other cellular targets such as toll like receptor 4 (via the suppression of both ligand-induced and ligand-independent oligomerization of TLR4) [32] and tubulin [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that NLRP3 inflammasome activation is associated with cerulein-induced inflammation in acini and suppressed by SFN. Earlier reports have suggested that SFN inhibited caspase-1 cleavage and IL-1 β maturation for the NLRP1b, NLRP3, NAIP5/NLRC4, and AIM2 inflammasomes in immune cells [18]. This study, for the first time, has demonstrated that SFN blocked the NLRP3 inflammasome activation in cerulein-induced pancreatic acini.…”
Section: Discussionsupporting
confidence: 53%
“…SFN is known to be important in the maintenance of cellular redox balance [14] and has earlier been used as an effective phytochemical antioxidant in studies of gastrointestinal and pulmonary diseases [1517]. In addition, SFN has been reported to inhibit multiple inflammasomes in immune cells [18]. Recent findings indicate that the nucleotide-binding domain leucine-rich repeat containing family, pyrin domain-containing 3 (NLRP3) inflammasome, provides the link between acinar cell death and inflammation during the development of AP; and activation of NLRP3 inflammasome is involved in the development of AP [19], which is inhibited by antioxidants like hydrogen-rich saline [12].…”
Section: Introductionmentioning
confidence: 99%
“…-/-mice Although the Keap1-Nrf2 pathway is a well-known target of sulforaphane, this isothiocyanate has also been reported to modulate different biological pathways independent of the Keap1-Nrf2 pathway (24,25). To determine whether the anti-obesity and insulin-sensitizing effects of glucoraphanin are mediated through Nrf2, the effects of glucoraphanin on energy balance and glucose metabolism were assessed in NC-and HFD- Fig.…”
Section: Glucoraphanin Does Not Exert Anti-obesity and Insulin-sensitmentioning
confidence: 99%